2019
DOI: 10.1002/stem.3116
|View full text |Cite|
|
Sign up to set email alerts
|

Human iPSC differentiation to retinal organoids in response to IGF1 and BMP4 activation is line- and method-dependent

Abstract: Induced pluripotent stem cell (iPSC)-derived retinal organoids provide a platform to study human retinogenesis, disease modeling, and compound screening. Although retinal organoids may represent tissue structures with greater physiological relevance to the in vivo human retina, their generation is not without limitations. Various protocols have been developed to enable development of organoids with all major retinal cell types; however, variability across iPSC lines is often reported. Modulating signaling path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 28 publications
0
42
0
Order By: Relevance
“…In the absence of vascularized stem cell-derived retinal organoids, bioreactors help facilitate this mechanism. A number of teams have also very recently come up with methods that lead to better cone and rod specification in human retinal organoids [57,[210][211][212][213].…”
Section: Improved Retinal Organoid Modellingmentioning
confidence: 99%
“…In the absence of vascularized stem cell-derived retinal organoids, bioreactors help facilitate this mechanism. A number of teams have also very recently come up with methods that lead to better cone and rod specification in human retinal organoids [57,[210][211][212][213].…”
Section: Improved Retinal Organoid Modellingmentioning
confidence: 99%
“…Nevertheless, a wide variability in differentiation efficiency across hiPSC lines is often reported (Capowski et al, 2019;Cora et al, 2019;Mellough et al, 2019;Chichagova et al, 2020). Chichagova et al (2020) have shown that the ability of three different hiPSC lines to differentiate into retinal organoids in response to IGF1 or BMP4 activation was line-and method-dependent. Hallam et al (2018) differentiated five hiPSC lines with a variability in efficiency, but by 5 months of differentiation all the retinal organoids were able to generate light responses and contained a well-formed ONL with PRCs containing inner segments, cilia, and outer-like segments.…”
Section: Human-derived Retinal Modelsmentioning
confidence: 99%
“…Since the first one, numerous groups have adapted or created their own method to more efficiently generate well laminated retinal organoids ( Meyer et al, 2011 ; Nakano et al, 2012 ; Zhong et al, 2014 ; Luo et al, 2018 ; Ovando-Roche et al, 2018 ). Nevertheless, a wide variability in differentiation efficiency across hiPSC lines is often reported ( Capowski et al, 2019 ; Cora et al, 2019 ; Mellough et al, 2019 ; Chichagova et al, 2020 ). Chichagova et al (2020) have shown that the ability of three different hiPSC lines to differentiate into retinal organoids in response to IGF1 or BMP4 activation was line- and method-dependent.…”
Section: Human-derived Retinal Modelsmentioning
confidence: 99%
“…Several reports, including those from the laboratory of Lyle Armstrong (Newcastle University, UK), have described variable laminar organization between samples differentiated from the same iPSC line and the presence of non‐neural cell types within retinal structures . To explore the possible roots of the observed variation, Chichagova et al assessed the ability of human iPSCs to generate retinal organoids through the application of differentiation protocols based on the modulation of BMP4 or IGF1 signaling and evaluated differentiation efficiency by monitoring morphological changes, gene and protein expression, and functional alterations . Interestingly, while the authors of this recent STEM CELLS article readily generated retinal organoids via both methodologies, the two different approaches produced a bias toward certain retinal cell types, including the preferential generation of rods, cones, and amacrine cells, as shown in the figure.…”
Section: Featured Articlesmentioning
confidence: 99%
“…Furthermore, these highly specialized cell types must also undergo detailed evaluations with regard to their functional similarities to endogenous cell types before being considered for transplantation into human patients suffering from various retinal degenerative states. In our second Featured Article published in STEM CELLS this month, Chichagova et al establish the need for careful consideration when selecting a protocol for retinal organoid formation by highlighting the dependence of overall efficiency on the signaling pathways modulated after their exploration of BMP4‐ or insulin‐like growth factor 1 (IGF1)‐dependent protocols . In a Related Article published in STEM CELLS Translational Medicine , Eastlake et al highlighted the therapeutic potential of transplanting Müller glia isolated from iPSC‐derived retinal organoids as a means to restore lost visual function in a mouse model of retinal degeneration …”
mentioning
confidence: 99%